2012
DOI: 10.1016/j.jmb.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of DNA-Bound Human Topoisomerase II Alpha: Conformational Mechanisms for Coordinating Inter-Subunit Interactions with DNA Cleavage

Abstract: Type II topoisomerases are required for the management of DNA superhelicity and chromosome segregation, and serve as frontline targets for a variety of small-molecule therapeutics. To better understand how these enzymes act in both contexts, we determined the 2.9-Å-resolution structure of the DNA cleavage core of human topoisomerase IIα (TOP2A) bound to a doubly nicked, 30-bp duplex oligonucleotide. In accord with prior biochemical and structural studies, TOP2A significantly bends its DNA substrate using a bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
205
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(213 citation statements)
references
References 94 publications
8
205
0
Order By: Relevance
“…2a (Stage 0), gyrase forms two chambers, with the top chamber open and the lower C chamber closed. When DNA enters the upper chamber (Stage 1), it is drawn to the floor, which bends DNA into a V shape caused by two 75°bends on opposing sides of the DNA cleavage site (Wendorff et al 2012). DNA bending orients the DNA arms so that they compete with GyrA CTD for DNA binding and formation of a chiral (+) loop on one pinwheel element.…”
Section: What Controls Supercoil Density?mentioning
confidence: 99%
“…2a (Stage 0), gyrase forms two chambers, with the top chamber open and the lower C chamber closed. When DNA enters the upper chamber (Stage 1), it is drawn to the floor, which bends DNA into a V shape caused by two 75°bends on opposing sides of the DNA cleavage site (Wendorff et al 2012). DNA bending orients the DNA arms so that they compete with GyrA CTD for DNA binding and formation of a chiral (+) loop on one pinwheel element.…”
Section: What Controls Supercoil Density?mentioning
confidence: 99%
“…Accordingly, docking studies at other possible binding sites were performed, which revealed a binding domain close to etoposide binding site in the central domain of hTopoIIα (PDB ID: 4FM9). 24 However, these compounds are not hTopoIIα poisons like etoposide. 25 Hence, the interactions of these compounds are expected to be different from that of etoposide.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…Topo II-α (9) is a commonly used proliferation marker that serves a function in DNA replication and chromosomal segregation by unwinding the DNA double helix. It is crucial for the active survival of cells and represents a common biomarker and target for multiple anticancer agents (30,31). Determination of Topo II-α expression facilitates the prognosis of overall survival rates of patients and their reaction to therapy (32).…”
Section: Discussionmentioning
confidence: 99%